2013
DOI: 10.1021/es4016475
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Polychlorinated Dibenzo-p-dioxins and Dibenzofurans, Dioxin-like Polychlorinated Biphenyls, and Polychlorinated Naphthalenes in Workplaces of Secondary Nonferrous Metallurgical Facilities in China

Abstract: ABSTRACT:The concentrations of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), dioxin-like polychlorinated biphenyls (dl-PCBs), and polychlorinated naphthalenes (PCNs) were determined in workplace air from eight secondary nonferrous metal processing plants to investigate occupational exposure to these toxic compounds. The total estimated daily intakes of PCDD/Fs and dlPCBs for workers by inhalation in the workplace were in the range of 0.15−9.91 and 0.13−8.59 pg of WHO-TEQ/kg of body weight (bw)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Although there were also large variation in the UP-POPs concentrations in the stack gases emitted from different plants (Hu et al, 2013a), we found that there were clear correlations between the ambient air and the stack gas concentrations of the PCDD/Fs, dl-PCBs and PCNs among the five investigated plants, respectively (Fig. 1).…”
Section: The Relationship Between Up-pops Concentrations In the Ambiementioning
confidence: 77%
See 3 more Smart Citations
“…Although there were also large variation in the UP-POPs concentrations in the stack gases emitted from different plants (Hu et al, 2013a), we found that there were clear correlations between the ambient air and the stack gas concentrations of the PCDD/Fs, dl-PCBs and PCNs among the five investigated plants, respectively (Fig. 1).…”
Section: The Relationship Between Up-pops Concentrations In the Ambiementioning
confidence: 77%
“…We have previously reported the details of the methods used to analyze the samples for UP-POPs (Guo et al, 2008;Hu et al, 2013a). Briefly, the samples were spiked with known amounts of 13 C 12 -labeled PCDD/Fs, 13 C 12 -labeled PCBs, and 13 C 10 -labeled PCNs, for use as internal standards (Table S1), then they were Soxhlet extracted with toluene for approximately 24 h. Each sample extract was concentrated and then subjected to a series of adsorption chromatography clean-up procedures, which were an acidified silica gel column, a multilayer silica gel column (filled, from top to bottom, with anhydrous sodium sulfate, 1 g activated silica gel, 8 g silica gel containing 44% (w/w) of H 2 SO 4 , 1 g activated silica gel, 5 g silica gel containing 33% (w/w) of 1 M NaOH, 1 g activated silica gel, 2 g of silica gel containing 10% (w/w) of AgNO 3 , and 1 g activated silica gel), and a basic alumina column.…”
Section: Sample Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The release of PCDD/Fs from a metal smelter might cause increased risks to workers in the metallurgical industry (Hu et al 2013a). The exposure of metallurgical smelting workers to PCDD/Fs has been assessed in several studies (Abballe et al 2013;Hu et al 2013a; Lee et al 2009;Shih et al 2008).…”
Section: Introductionmentioning
confidence: 99%